Evaluating the Value of Vegetation Ecosystem Services in District 16 of Tehran Municipality using the i-Tree Model - Hossein Vahidi; Majid Ramezani Mehrian; Amin Jalayer; Mohsen Esfahani Zadeh; Azadeh Ali Hosseini (Environmental Energy and Economic Research, 2023)
Awareness of the structure, function, and value of vegetation and green space in cities can improve management decisions related to human health and the condition of the environment. In 2015, an assessment of the vegetation in the Tehran urban vegetation was done. The i-Tree Eco model was used to evaluate data from 36 field plots situated throughout Tehran D16. This study assimilates the i-Tree Eco model to assess the value of vegetation ecosystem services in District 16 of Tehran Municipality, one of the greenest areas. Based on public trees managed by the district municipality, eliminated about 67 tons of pollutants in one year. This pollution reduction includes about 5 tons of CO, 13 tons of NO2, 8 tons of O3, 35 tons of PM10, and 15 tons of SO2. Two factors, including tree cover and concentrations of air pollutions, significantly affect air pollution removal. Urban trees have a critical role in mitigating air pollution. However, the limitations and increasing sources of production of pollutants, especially air pollutants, are not the only key to this trouble. Therefore, it is advised to increase the per capita and principled maintenance of public urban green space, along with indicators such as environmental characteristics, adjacent urban structures, street design, climate, and the most important plant species compatible with the region.